Enhanced power density in solid oxide fuel cells using nickel-assisted gadolinium-doped ceria anodes - Nacer Badi; Aashis S. Roy; Raghavendra Sagar; Saleh A. Alghamdi; Abdulrhman M. Alsharari; Alex Ignatiev (PLoS ONE, 2025)
This study demonstrates the use of Gadolinium-doped ceria (GDC) (Ce₀.Gd₀.₂O₂) as the anode, BaNb₄MoO₂₀ (BNMO) as the electrolyte, and Lanthanum strontium cobalt oxide (LSCO) (La₀.Sr₀.₄CoO₃) as the cathode in the fabrication of a solid oxide fuel cell (SOFC). The synthesized nanocomposites were characterized using Fourier-transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD) for structural analysis, and scanning electron microscopy (SEM) for surface morphology assessment. DC conductivity measurements revealed that LSCO exhibited a high conductivity of 5.2 S/cm, attributed to the efficient flow of electrons through the electrolyte, highlighting its potential as a promising cathode material. Nyquist plots displayed semi-circular arcs, which correspond to distinct electrochemical processes within the system. The diameter of these arcs reflects the charge transfer resistance, primarily due to grain boundary resistance, while the initial resistance preceding the arc is associated with the bulk properties of the electrolyte. Beyond the first semicircle, diffusion resistance increases with frequency as a result of electrode polarization. It was also observed that the cell voltage dropped in discrete steps when the current density reached 200 mA/cm2. Specifically, the voltage decreased from 0.75 V to 0.53 V at 500°C, and from 0.98 V to 0.73 V at 800°C, likely due to charge transfer resistance at the electrode-electrolyte interface. The power density curve indicated that the cell achieved power densities of approximately 0.094, 0.118, 0.146, and 0.184 W/cm2 at operating temperatures of 500, 600, 700, and 800°C, respectively, demonstrating favorable performance for an SOFC employing BNMO as the electrolyte.